Pengaruh Optimisme dan Resiliensi Akademik untuk Meningkatkan Subjective Well Being pada Mahasiswa yang Menjalani Perkuliahan Daring - P, Nourma Ayu S; Nawangsih, Riska Anggita (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2021)
This study aims to see the influence of optimism and resilience academic in improving subjective well being in university students who lead a lecture online. The research method used is quantitative methods with the amount of 108 students Unimuda Sorong. Data were collected using a scale of optimism, the scale of academic resilience and the scale of subjective well being that is presented in the form of a google form. The scale of optimism using the scale from Seligmen which consists of three aspects, namely permanent, pervasiveness, and personalization. The scale of academic resilience use of the academic resilience scale-30 (ARS-30) developed by Cassidy. The scale of subjective well being using the college students subjective well-being questionnaire - revised (CSSWQ-R) which was adopted from the Renshaw. Analysis of the data used in this research is multiple linear regression analysis. The results of the study showed that optimism and resilience simultaneously provide a positive and significant influence on subjective well being in university students who lead lectures online with the value of F 33,107 and the significance of 0,000 (<0,05). Based on the results of T-test showed that partial resilience academic has a positive and significant influence on subjective well being of students with a significance value of 0,000 (<0,05), while optimism has a positive influence but not significant to the improvement of subjective well being of students with a significance value 0,447 (>0,05). Keywords : Optimism, Rsiliensi Academic, Subjective Well Being